Disciplinary action against government servants and its remedies - Srivastava, Kripa Dayal (Lucknow, 1970)
It gives us a great pleasure to place the third edition of our book before the public. With the growth and complexities of employment under the State, the importance of the subject dealt with in the book is increasing every day. Because of the limited scope of the book, it has not been possible to deal with all the aspects of conditions of employment under the State, but in so far as any aspect of employment relates to punishment, it has been found necessary to discuss the same. Apart from the guarantee of employment, embodied in the Constitution, the infringement of rules, resulting in an injury to an employee being also justiciable, the scope of the subject-matter of the book has widened. As is well known, administrative finality and guaranteed fundamental rights are irreconcilable, where limitation on these rights are made justiciable. Administrative actions also, where a lis is involved, have to conform to the rules of natural justice. As a matter of fact. there is no administrative finality where the recognised rights of citizen, sub ject to the limitations conferred by law, are affected.